School Schedule and the Gender Pay Gap - Emma Duchini; Clémentine Van Effenterre (Institute of Labor Economics (IZA), 2020)
We provide causal evidence that children's school schedules contribute to the persistence of the gender pay gap between parents. Historically, French children have had no school on Wednesdays. In 2013, a reform reallocated some classes to Wednesday mornings. Exploiting variations in the application of this reform over time and across the age of the youngest child, we show that mothers are more likely to adopt a regular Monday-Friday full-time working schedule after the reform, while fathers' labor supply is unchanged. Consequently, the reform decreased the monthly gender pay gap by 6 percent, generating fiscal revenues that substantially outweigh its costs.
Keywords: H52; J13; J16; J22; 330; school schedule; gender inequality; female labor supply; child penalty